Maos Qurâ€™an: Android Device Technology for Primary School Students to Khataman Juz ’Amma Online - Muzaqi, Sugito; Darujati, Cahyo; Gumelar, Bimo; WiwohoMudjanarko, Sri; IkhsanSetiawan, M. (International Journal of Engineering and Technology, 2019)
The globalization in the IT world is very influential on the behavior of someone who is looking for identity in everyday life one is in the area of AL QURâ€™AN which is now very rarely people interested to make AL QURâ€™AN reading material, rote or finish. Collaboration between IT with AL QURâ€™AN at the moment is mostly done as a breakthrough to make perfect beings. Use of this application is based on the fact that when primary school at this time like to play android device, then the researchers tried to make an Maos AL QURâ€™AN application that could be used by primary school learn Al Quran start read, memorize and finish with easy and fun way. The purpose of the research was to design a software and make desktop applications on a Smartphone could be a medium of learning the AL QURâ€™AN applications based on android is offline to facilitate all activities in reading, memorizing and finishing Juz 'Amma.Â Juz 'Amma is juz last thirty juz of AL-QURâ€™AN. The main characteristic is the short surah, with beautiful language charming, touching hearts or rebuke accompanied by rational arguments capable of convincing reasoning that has not been churned up by ambiguous way of thinking or subjectivity view. Speech Recognition Technology (Automatic Speech Recognition or Computer Speech Recognition), could convert spoken words into text. The term "voice recognition" was used to refer to the recognition system had to be trained for a particular speaker, as a special case for the introduction of most desktop software.Â Â